Integrated Risk Governance Science Plan and Case Studies of Large-scale Disasters - Shi, Peijun; Jaeger, Carlo; Ye, Qian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
"Integrated Risk Governance: Science Plan and Case Studies of Large-scale Disasters" is the first book in the IHDP-Integrated Risk Governance Project Series. It consists of two parts: Part I: Integrated Risk Governance Project Science Plan, which outlines the challenge, research programme, outcomes, and implementation strategy of the IRG Project; and Part II: Case Studies of Large-scale Disasters, which includes case analyses of experience, lessons learned and recommendations on various large-scale disasters around the world, such as the Tangshan and Wenchuan earthquakes and the great ice storm in China, European heat waves, and Hurricane Katrina in the USA. The community model of integrated natural disaster risk governance and paradigm of catastrophe risk governance in China are also presented. Prof. Peijun Shi works at Beijing Normal University, China; Prof. Carlo Jaeger works at Potsdam Institute for Climate Impact Research, Germany; Prof.Qian Ye works at Beijing Normal University, China.
Part I: Integrated Risk Governance Project (IRG) Science Plan -- Executive Summary -- The Challenge -- Research Programme -- Outcomes -- Implementation Strategy -- Part II: Integrated Governance of Large Scale Disaster Risk -- Experiences and Lessons of Large-Scale Disaster Governance in China $1 (BPerspective to the Response of Wenchuan Earthquake Disaster May 12 2008 -- Experiences and Lessons of Large-Scale Disaster Governance in China $1 (BPerspective to the Response of Freezing Rain and Snowstorm Disaster in South China Early 2008 -- Avoiding the Avoidable. Towards A European Heat Waves Risk Governance -- Hurricane Katrina: A Teachable Moment -- China Wenchuan and Tangshan Earthquakes$1 (BOpportunity for Learning and Development -- Comparative Case Study of Entry Transition of Large-scale Disasters: 2008 South China Snow Storm and 2005 US Katrina -- Chinese Paradigm of Catastrophe Risk Governance -- The Community Model of Integrated Natural Disaster Risk Prevention in China.s
Keywords: Geography; Geology; Regional planning; System safety; Climatic changes; Environmental economics; Earth Sciences; Natural Hazards; Climate Change; Landscape/Regional and Urban Planning; Quality Control, Reliability, Safety and Risk; Environmental Economics